Antifungal activity of copper oxide nanoparticles derived from Zizyphus spina leaf extract against Fusarium root rot disease in tomato plants - Sozan E. El-Abeid; Mohamed A. Mosa; Mohamed A. M. El-Tabakh; Ahmed M. Saleh; Mohamed A. El-Khateeb; Maha S. A. Haridy (Journal of Nanobiotechnology, 2024)
Abstract Incorporating green chemistry concepts into nanotechnology is an important focus area in nanoscience. The demand for green metal oxide nanoparticle production has grown in recent years. The beneficial effects of using nanoparticles in agriculture have already been established. Here, we highlight some potential antifungal properties of Zizyphus spina leaf extract-derived copper oxide nanoparticles (CuO-Zs-NPs), produced with a spherical shape and defined a 13–30 nm particle size. Three different dosages of CuO-Zs-NPs were utilized and showed promising antifungal efficacy in vitro and in vivo against the selected fungal strain of F. solani causes tomato root rot disease, which was molecularly identified with accession number (OP824846). In vivo  results indicated that, for all CuO-Zs-NPs concentrations, a significant reduction in Fusarium root rot disease occurred between 72.0 to 88.6% compared to 80.5% disease severity in the infected control. Although treatments with either the chemical fungicide (Kocide 2000) showed a better disease reduction and incidence with (18.33% and 6.67%) values, respectively, than CuO-Zs-NPs at conc. 50 mg/l, however CuO-Zs-NPs at 250 mg/l conc. showed the highest disease reduction (9.17 ± 2.89%) and lowest disease incidence (4.17 ± 3.80%). On the other hand, CuO-Zs-NPs at varied values elevated the beneficial effects of tomato seedling vigor at the initial stages and plant growth development compared to either treatment with the commercial fungicide or Trichoderma Biocide. Additionally, CuO-Zs-NPs treatments introduced beneficial results for tomato seedling development, with a significant increase in chlorophyll pigments and enzymatic activity for CuO-Zs-NPs treatments. Additionally, treatment with low concentrations of CuO-Zs-NPs led to a rise in the number of mature pollen grains compared to the immature ones.  however the data showed that CuO-Zs-NPs have a unique antifungal mechanism against F. solani, they  subsequently imply that CuO-Zs-NPs might be a useful environmentally friendly controlling agent for the Fusarium root rot disease that affects tomato plants. Graphical Abstract